Congruência e aplicações - Medeiros, José Marcondes Gomes de (2015)
In this paper we make a brief study about arithmeti number theory, in parti ular, modular ongruen e and whole primality tests. O des ribe arefully the iphering and de iphering method of RSA en ryption and dis uss some nuan es of RSA. Therefore, this study a little about Gauss, the prin e of mathemati ians, in whi h many of his ideas are very important and the basis for the development of number theory, to the present day.